Modern Understanding of Severe Bronchial Asthma - A. Yu. Kraposhina; E. A. Sobko; I. V. Demko; A. B. Katser; O. V. Kazmerchuk; Yu. I. Abramov (SINAPS LLC, 2022)
The review provides data on severe bronchial asthma. Frequent exacerbations of asthma significantly reduce the quality of life of patients, cause disability, disability and death. The heterogeneity of severe bronchial asthma fits into the concepts of phenotype and endotype, the identification of which in clinical practice has limitations, but is necessary for personalized therapy. Analysis of the literature reflecting experience in patient data management is needed to form holistic perceptions of severe bronchial asthma and develop ways to optimize therapy.